Analisis Literatur terkait dengan Model Pemimpin dan Kepemimpinan dalam Islam (Kasus Penggabungan Tiga Bank Syariah Besar Menjadi BSI) - Dina Arfianti Siregar; Marlya Fatira AK; Nur Ahmadi; Hendri Tanjung (PT. PENERBIT TIGA MUTIARA, 2024)
This article is about a literature review regarding good leadership models in Islam as seen from the experience of the merger of 3 (three) Sharia Banks in Indonesia to become Bank Syariah Indonesia (BSI), which is currently approximately three years old and the Indonesian Sharia banking market until compete and occupy the position as a sharia bank with the most significant asset position compared to 6 (six) other conventional banks which have dominated the Indonesian market for decades. The type of data used in this research is qualitative data, with the data source coming from secondary sources and the data collection technique used being a documentation technique through literature review using the Systematic Literature Review (SLR) data analysis technique by utilizing the Published or Perish (POP) metadata tool and VOS Viewer. The research method used is a qualitative method, with research results showing that the leadership model of Bank Syariah Indonesia has accommodated the best leadership criteria in Islam, which can be adaptive, fast response, and solutions while still implementing the traits and characteristics of leaders who are sincere, trustworthy, Katonah, and tabligh. This leadership character was demonstrated by leading the previous three large banks into one with one vision, mission, and work culture, as well as the synergy of all human resources that supported joint achievements to success in the three years of its existence.